2018
DOI: 10.4111/icu.2018.59.5.342
|View full text |Cite
|
Sign up to set email alerts
|

Infection following penile prosthesis placement at an academic training center remains low despite involvement of surgeons-in-training

Abstract: PurposePrimary care providers harbor misconceptions regarding penile prosthetic surgery, largely overestimating the rate of infection. Rates of infection following surgery for primary placement and revision are estimated as 1% to 3% and 10% to 18%, respectively. Our objective was to determine the contemporary incidence of infection following inflatable penile prostheses surgery at an academic training center where surgeons-in-training are routinely involved.Materials and MethodsReview of a prospectively collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 28 publications
(31 reference statements)
0
4
1
2
Order By: Relevance
“…Similar to previous reports, we did not find any correlation between patient age, history of urinary diversion, history of pelvic radiotherapy, obesity, and EPI. 12 24 25 26 27 28 29 30 31 32 33 Furthermore, we failed to find any association between EPI and active smoking status. Despite this, the negative effect of tobacco smoking in the immediate postoperative setting has been well documented.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Similar to previous reports, we did not find any correlation between patient age, history of urinary diversion, history of pelvic radiotherapy, obesity, and EPI. 12 24 25 26 27 28 29 30 31 32 33 Furthermore, we failed to find any association between EPI and active smoking status. Despite this, the negative effect of tobacco smoking in the immediate postoperative setting has been well documented.…”
Section: Discussioncontrasting
confidence: 58%
“…This finding is similar to that reported by McAbee et al . 28 from an academic training center, where the rate of infections following PP placement remained low despite involvement of surgeons-in-training.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, academic institutions have implanted significant numbers of penile prostheses. The experience of surgeons-in-training and their participation in IPP implantation did not increase the rate of postoperative IPP infection in a recent retrospective review, of a high-volume implanter in an academic setting [72]. A review of the New York Statewide Planning and Research Cooperative System database revealed 14,969 men who underwent IPP placement between 1995 and 2014.…”
Section: Surgical Factorsmentioning
confidence: 99%
“…A previous study by Nieder et al reported that the rate of complications after transurethral bladder tumor resection, the rate of complications was 5.8% for both fellow and resident trainees under supervision. 37 However, the authors reported that the rates of complications and bladder perforation could be more frequent with senior urologists than trainees, however, no statistical analysis was done. Moreover, McAbee et al reported that the rate of infection was 0.3% only following penile prosthesis placement surgeries.…”
Section: The Risk To Develop Complicationsmentioning
confidence: 99%